1999
DOI: 10.1590/s0101-81751999000100003
|View full text |Cite
|
Sign up to set email alerts
|

Sazonalidade e horário de atividade de abelhas Euglossinae (Hymenoptera, Apidae), em florestas de terra firme na Amazônia Central

Abstract: Mareio Lu iz de Olivei ra 2, 3 ABSTRACT. Seasonality and daily activity of Euglossinae bees (Hymenoptera, Apidae) in terra firme forest in Central Amazonia. Euglossinae bee fauna oftwo areas of terra firme forest near Manaus, Amazonas, Brazil was compared. Ove r a twelve-month period collections were done r0l1nightly, between 7:00 a.m and 5:00 p.m, using traps wilh eight kinds ofscent bails. The traps were placed in lhe underslory and in tree crowns. The majority of species and specimens was most active bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
1
15

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 15 publications
(2 reference statements)
1
21
1
15
Order By: Relevance
“…Embora as comparações entre os trabalhos, principalmente em relação à riqueza e abundância, devam ser feitas de forma cautelosa devido à falta de padronização dos métodos (MORATO 1998), o número de espécies encontrado neste estudo pode ser considerado representativo da comunidade local de Euglossini, quando comparado à fauna desse grupo de abelhas amostrada em pesquisas realizadas em alguns ecossistemas da Região Nordeste, Sul e Sudeste do Brasil (RAW 1989;WITTMANN et al 1988;REBÊLO & GARÓFALO 1991;PERUQUETTI et al 1999;NEVES & VIANA 1997, 1999JESUS 2000). Porém, pode ser considerada pobre quando comparada aos levantamentos realizados nas florestas úmidas da América Central e Região Amazônica (PEARSON & DRESSLER 1985;ROUBIK & ACKERMAN 1987;MORATO & CAMPOS 1992;OLIVEIRA & CAMPOS 1995;, onde o número de espécies amostradas foi, na maioria dos casos, bem maior do que o obtido neste trabalho.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Embora as comparações entre os trabalhos, principalmente em relação à riqueza e abundância, devam ser feitas de forma cautelosa devido à falta de padronização dos métodos (MORATO 1998), o número de espécies encontrado neste estudo pode ser considerado representativo da comunidade local de Euglossini, quando comparado à fauna desse grupo de abelhas amostrada em pesquisas realizadas em alguns ecossistemas da Região Nordeste, Sul e Sudeste do Brasil (RAW 1989;WITTMANN et al 1988;REBÊLO & GARÓFALO 1991;PERUQUETTI et al 1999;NEVES & VIANA 1997, 1999JESUS 2000). Porém, pode ser considerada pobre quando comparada aos levantamentos realizados nas florestas úmidas da América Central e Região Amazônica (PEARSON & DRESSLER 1985;ROUBIK & ACKERMAN 1987;MORATO & CAMPOS 1992;OLIVEIRA & CAMPOS 1995;, onde o número de espécies amostradas foi, na maioria dos casos, bem maior do que o obtido neste trabalho.…”
Section: Discussionunclassified
“…Esses dados são semelhantes aos obtidos por outros estudos que também empregaram o eucaliptol (RAW 1989;AGUILAR 1990;NEVES & VIANA 1997, 1999BEZERRA & MARTINS 2001).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Ackerman (1983) showed that capture rates using artifi cial baits refl ect actual bee abundance and baiting studies are therefore a widely applied measure of euglossine bee diversity and abundance. Studies in South and Central America have investigated the effect on euglossine communities from different habitats (Dressler 1985, Oliveira & Campos 1995, seasonality (Janzen et al 1982, Ackerman 1983, Oliveira 1999, fragmentation (Becker et al 1991, Tonhasca et al 2002, and agricultural effects (Otero & Sandino 2003, Hedström et al 2006a, providing information on the community structure and habitat changes. However, none of these studies addressed the community change between reforested and managed continuous forest patches.…”
mentioning
confidence: 99%
“…This species was recently recorded in the central Pacific plain of Colombia, Chocó region (Otero & Sandino 2003), and also in the French Guiana and Ecuador (Dick et al 2004). In Brazil, several males were collected in the states of Pará (Ducke 1901, Kimsey 1982, Amazonas (Braga 1978, Kimsey 1982, Becker et al 1991, Oliveira 1999, Amapá (Kimsey 1982, Moure et al 2007, and more recently in Maranhão (Rebêlo 2001, Brito & Rêgo 2002. Nevertheless, Kimsey (1982) pointed out that this species was also recorded in southern Brazil, in São Paulo state (São Paulo city).…”
mentioning
confidence: 95%